A sensory neuroprosthesis enhances recovery from treadmill-induced stumbles for individuals with lower limb loss - Suzhou Li; Ronald J. Triolo; Hamid Charkhkar (Scientific Reports)
Abstract Over 50% of individuals with lower limb loss report a fear of falling and avoiding daily activities partly due to a lack of plantar sensation. Providing direct somatosensory feedback via neural stimulation holds promise for addressing this issue. In this study, three individuals with lower limb loss received a sensory neuroprosthesis (SNP) that provided plantar somatosensory feedback corresponding to prosthesis-floor interactions perceived as arising from the missing foot generated by electrically activating the peripheral nerves in the residuum. Participants walked on a treadmill while receiving perturbations involving brief increases in the belt speed. Perturbations were initiated during early stance and randomly delivered to intact and prosthetic sides with the SNP active or inactive. With the SNP active, participants exhibited decreased trunk angular sway and peak trunk flexion angular velocity during recovery from both prosthetic and intact side perturbations. For prosthetic side perturbations, peak ground reaction force magnitudes decreased when the SNP was active. For intact side perturbations, peak ground reaction force magnitudes increased on the prosthetic side’s first recovery step after the perturbation, which resulted in a more symmetric recovery because the force approached the response on the intact side’s first recovery step following a prosthetic side perturbation. These results suggest participants integrated the feedback from the SNP into their sensorimotor control for maintaining stability and gained confidence in relying on their prosthetic limb during recovery. Restoring plantar sensation with a SNP for individuals with lower limb loss could lead to reduced risk of falling by improving recovery from trips.